Jessie Conlisk: capstone - Conlisk, Jessie, artist (Colorado State University. Libraries, 2024)
The artist's statement: Art has long served as an integral aspect of my identity, shaping my journey from early immersion in art classes at the age of 9, to my current pursuit of artistic development. In high school, I took an Art concentration pathway, which solidified my aspiration to forge a career in Graphic Design. While Graphic Design remains my primary focus, my artistic exploration extends across diverse mediums encompassing drawing, painting, and 3D design. During my time at Colorado State University, I have diligently honed my craft through various art courses, striving for mastery in each endeavor, and a pivotal moment in my artistic evolution occurred during my Study Abroad experience in Florence, Italy, in the Spring of 2023. Immersed in painting, drawing, and art history courses, I absorbed invaluable insights and techniques from The Great Masters, profoundly enriching my understanding of artistic techniques. My artistic evolution has witnessed a harmonious fusion of traditional artistry with contemporary Graphic Design, as a result, I have learned how to integrate my traditional work into my Graphic Designs. While I am proud of what I have achieved thus far, my artistic career has just begun, and I look forward to seeing how it will continue to develop.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: graphic design